Strategi Pengembangan Usaha Industri Rumah Tangga Tempe di Desa Sendang Mulya Sari Kabupaten Konawe : (Studi Kasus Usaha Tempe Bu Ratmi) - Sinta Dewi; Sara Evi Rahayu (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The purpose of this study was to analyze internal and external strategies in the development of the tempeh industry in Sendang Mulya Sari Village, Tonggauna District, Konawe Regency. The determination of the research sample was carried out intentionally (purposive sampling) using key informants, in this study the key informant was Mrs. Ratmi, the owner of the tempeh business. This study is a qualitative descriptive study using analysis tools, namely SWOT. The development strategy of the "Mrs. Ratmi" tempeh industry business in Sendang Mulya Sari Village, Tongauna District, Konawe Regency is in quadrant I, namely the SO = 4.14 strategy, which is a very profitable position for the company because at this time the tempeh business has opportunities and strengths that can be utilized. The strategy that must be carried out in this condition is to change the old strategy. The strategy that must be applied in this condition is to support an aggressive growth policy (Growth oriented strategy) so that it can increase the income of tempeh entrepreneurs.